Auditory- Verbal Therapy: A Systematic Review for the Effectiveness of Intervention in Children with Hearing Loss - Binos, Paris; Charalambous, Marina; Minaidou, Despo (My University, 2020)
This systematic review was designed to investigate the effectiveness of auditory-verbal therapy (AVT) based on recent research findings of the literature. AVT is seen today as the primary treatment approach for developing spoken language in children with cochlear implants despite the debate about educational options for these children. The AVT effectiveness should be examined by systematic reviews. The present review was conducted following PRISMA guidelines (preferred reporting items for systematic reviews). Search terms were chosen based on the research question and used in a search in PubMed/Medline. Last decade’s published peer-reviewed papers meeting inclusion criteria were reviewed. The reviewed articles measured many levels of language development and parent’s use of alternative communication models. The result of this review reveals AVT as an important clinical approach that improves young cochlear implant (CI) children to outperform peers in bilingual-bicultural programs in receptive vocabulary and speech perception or at the least be at a similar level on speech, language and self-esteem. Other aspects related with voice seemed also benefited, placing young CIs in the normal range for receptive vocabulary development. Less improvement noted in the area of reading. AVT approach can positively assist infants develop spoken language and support full integration into mainstream society despite the limited evidences presented. This position is supported by research findings of young CIs comparable to their hearing peers. Overall studies suggest AVT as a positive clinical approach for spoken language of young CIs and provide evidences that there is no advantage for the use of other alternative communication models before or after CI.
Keywords: Cochlear implants; AVT; Hearing impairment